Cytokine Storm in COVID-19: The Current Evidence and Treatment Strategies - Tang, Yujun; Liu, Jiajia; Zhang, Dingyi; Xu, Zhenghao; Ji, Jinjun; Wen, Chengping (Frontiers in Immunology, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2) is the pathogen that causes coronavirus disease 2019 (COVID-19). As of 25 May 2020, the outbreak of COVID-19 has caused 347,192 deaths around the world. The current evidence showed that severely ill patients tend to have a high concentration of pro-inflammatory cytokines, such as interleukin (IL)-6, compared to those who are moderately ill. The high level of cytokines also indicates a poor prognosis in COVID-19. Besides, excessive infiltration of pro-inflammatory cells, mainly involving macrophages and T-helper 17 cells, has been found in lung tissues of patients with COVID-19 by postmortem examination. Recently, increasing studies indicate that the "cytokine storm" may contribute to the mortality of COVID-19. Here, we summarize the clinical and pathologic features of the cytokine storm in COVID-19. Our review shows that SARS-Cov-2 selectively induces a high level of IL-6 and results in the exhaustion of lymphocytes. The current evidence indicates that tocilizumab, an IL-6 inhibitor, is relatively effective and safe. Besides, corticosteroids, programmed cell death protein (PD)-1/PD-L1 checkpoint inhibition, cytokine-adsorption devices, intravenous immunoglobulin, and antimalarial agents could be potentially useful and reliable approaches to counteract cytokine storm in COVID-19 patients.